Bisociative Knowledge Discovery : An Introduction to Concept, Algorithms, Tools, and Applications. - Berthold, Michael R. (Lecture Notes in Computer Science Series, 2012)
The focus of this book, and the BISON project from which the contributions originate, is a network based integration of data repositories of a variety of types, and the development of new ways to analyse and explore the resulting gigantic information networks.